COGNITIVE ENHANCING AND ANTIOXIDANT EFFECTS OF TELMISARTAN IN SCOPOLAMINE-INDUCED AMNESIC RATS - DEBASREE DEB; VEENA NAYAK; KL BAIRY; MOHANDAS RAO KG; SALINI S KOSHY (International Journal of Pharma and Bio Sciences, 2015)
Brain Renin Angiotensin System (RAS) is involved in the pathogenesis of Alzheimer’s disease (AD). Treatment with a RAS blocker thus may have beneficial effects in preventing the cognitive deficits of AD. The present study was designed to investigate the cognitiveenhancing activity ofa RAS blocker, telmisartan, in scopolamine-induced amnesic rats using the passive avoidance test. The study also analysed the antioxidant potential and acetylcholinesterase activity of telmisartan in mitigating the oxidative stress induced by scopolamine. Administration of scopolamine induced significant impairment of memory as indicated by a marked decrease in the step-through latency in the passive avoidance test which was reversed by pre-treatment with 3.60 mg/kg of telmisartan Moreover, treatment with 3.60 mg/kg telmisartanin scopolamine-induced amnesic rats significantly decreased malondialdehyde level which was accompanied by an increase in the activities or contents ofglutathione transferase, SOD and protein thiols.Further, the activity of acetylcholinesterase was significantly inhibited by telmisartan to a level similar to that observed in control rats.These data demonstrate that telmisartanhas potent cognitive-enhancing activity which may be attributed to its antioxidant properties or acetylcholinesterase inhibiting activity though other putative mechanisms need to be investigated.